Innovative Leadership in Driving Organizational Innovation and Performance A Systematic Literature Review - Heru Nugroho; Selamet Riyadi; Setyani Dwi Lestari; Slamet Mudjijah (Komunitas Dosen Indonesia, 2025)
This systematic literature review examines the role of innovative leadership in fostering organizational innovation and enhancing performance. Using the PRISMA framework, 131 relevant studies from 2015 to 2024 were analysed to explore the relationships between leadership styles, innovation processes, and organizational outcomes. The results highlight that transformational and creative leadership are pivotal in cultivating a culture of innovation by promoting knowledge sharing, employee engagement, and strategic adaptability. These leadership styles enable organizations to respond effectively to dynamic market demands and emerging challenges, such as digital transformation and sustainability. The study also emphasizes the importance of innovative leadership in achieving organizational performance by aligning strategies with innovation goals and improving overall adaptability. Emerging themes, including digital transformation, sustainability, and entrepreneurial leadership, illustrate the evolving demands placed on leaders in modern contexts. This review bridges gaps in the existing literature by providing a comprehensive synthesis of the impact of innovative leadership on both innovation and performance, while identifying key areas for future research. The findings contribute to the theoretical understanding of innovative leadership and offer practical insights for organizations seeking to thrive in competitive and fast-changing environments.